PEMBATALAN PERJANJIAN MAATSCHAP YANG DIDIRIKAN TANPA JANGKA WAKTU DAN ATAS DASAR WANPRESTASI - Putri Santika, Ni Luh; Ari Krisnawati, I G A A (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
This paper entitled “MAATSCHAP CANCELLATION WHICH IS ESTABLISHED WITHOUT PERIOD AND ON THE BASIC OF WANPRESTASI”. This paper uses normative analytical methods and the statute approach. Maatschap is the simplest form of cooperation to jointly find many advantages in society. As the agreement, then maatschap can be cancelled. There is possibilty maatschap without an agreed period before and the wanprestasi in the implementation, so it needs to be studied about maatschap cancellation terms of Indonesian Civil Code.
Keywords: Cancellation, Maatschap, Period, Wanprestasi.